Mediation effects of cognitive, physical, and motivational reserves on cognitive performance in older people - Cabaco, Antonio Sánchez; Wobbeking Sánchez, Marina; Mejía-Ramírez, Manuel; Urchaga-Litago, José David; Castillo-Riedel, Eduardo; Bonete-López, Beatriz (Frontiers in Psychology, 2023)
We study from a multidimensional perspective the different factors that help prevent the development of cognitive impairment in old aging. This study analyzed in 300 elderly subjects the relationship between cognitive reserve (CR), physical reserve (PR) and motivational reserve (MR) with cognitive impairment. This study also takes into consideration different variables (sex, age, educational level, and institutionalization) that might affect the results in the different types of reserves (CR, PR and MR) and cognitive impairment. The results show that people with a higher CR, PR and MR have less cognitive impairment. Therefore it is important to consider measuring the CR as an important variable to diagnose neurodegenerative illnesses but it is also essential to take into account the physical state and physical activity, as well as the motivational dimension